The Impact of Green Banking on the Stability and Profitability of Islamic Banking in Indonesia - Muhamad Haris; Nurwahidin; Veithzal Rivai Zainal (Journal Research of Social Science, Economics, and Management, 2026)
Green financing is a key instrument in the implementation of green banking, supporting environmental sustainability while also having the potential to influence banks' financial performance. This study analyzed the impact of green banking on the stability and profitability of Islamic banks in Indonesia. The sample comprised 17 Islamic commercial banks, yielding 97 bank-year observations over the 2019–2025 period. Annual data were obtained from the annual and sustainability reports of each bank. Green banking was proxied by the ratio of green financing to total financing, whereas bank stability and profitability were measured using the equity-to-total-assets (ETA) ratio and return on assets (ROA), respectively. The study employed fixed-effects panel data regression with standard errors clustered at the bank level. The results indicated that green financing had a positive and significant effect on bank stability but a negative and statistically insignificant effect on profitability. Banks with stronger capital adequacy and greater operational efficiency also exhibited higher levels of stability and profitability. These findings suggest that the benefits of green financing are reflected initially in enhanced bank resilience, whereas its effect on profitability may take longer to materialize. Therefore, Islamic banks should expand green financing in a prudent manner while continuing to strengthen their capital base, improve operational efficiency, and enhance financing risk management.